2004
DOI: 10.1136/gut.2003.038588
|View full text |Cite
|
Sign up to set email alerts
|

Real time high resolution magnetic resonance imaging for the assessment of gastric motility disorders

Abstract: Background: The aim of this study was to evaluate whether patients with increased or decreased gastric motility can be differentiated from healthy volunteers by means of real time magnetic resonance imaging (MRI). Patients and methods: Ten healthy volunteers, 10 patients with gastroparesis, and 10 patients with functional pylorospasm/peptic pyloric stenosis underwent real time MRI. All patients were examined on two separate days; once prior to therapy and once after adequate therapy. Antral motility was quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 32 publications
0
81
1
Order By: Relevance
“…Several research groups have reported that fluid motions in the stomach promote the emulsification of oil components and drug release from matrix tablets (Schwizer et al, 2006;Abrahamsson et al, 2005). Ajaj et al (2004) reported unusual peristaltic motions in gastroparesis patients having a decreased ACW speed or different degrees of ACW contractions, which were monitored by magnetic resonance imaging (MRI). However, the physical effects of gastric peristalsis on gastric digestion are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported that fluid motions in the stomach promote the emulsification of oil components and drug release from matrix tablets (Schwizer et al, 2006;Abrahamsson et al, 2005). Ajaj et al (2004) reported unusual peristaltic motions in gastroparesis patients having a decreased ACW speed or different degrees of ACW contractions, which were monitored by magnetic resonance imaging (MRI). However, the physical effects of gastric peristalsis on gastric digestion are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, magnetic resonance imaging (Ajaj et al, 2004), three-dimensional computed tomography, and single-photon emission computed tomography (SPECT) (Bouras et al, 2002) were used to assess the gastric accommodation reflex of the proximal stomach. However, no simple and useful method exists for the clinical evaluation of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, image analysis of MRI bowel data is a complicated, high workload process, which requires dedicated readers and sound statistical analysis (7)(8)(9)(10). The motion encoding technique known as tagged imaging or SPAMM (spatial modulation of the magnetization) was originally developed for cardiac motion (11,12) but has been increasingly used in the abdominal area for measurements of deformation of the liver, distension of the stomach, and gastric activity (13)(14)(15). In SPAMM, a short prepulse sequence periodically saturates the magnetization that will eventually appear as a line or tag pattern in the image.…”
mentioning
confidence: 99%